SCIENCE TEACHING FOR ALL OR FOR AN ELITE?: CONVERGING VIEWS FROM DIFFERENT THEORETICAL PERSPECTIVES - Alejandro Pujalte; Agustín Adúriz Bravo; Silvia Porro (Universidad Nacional del Nordeste, 2015)
It has been repeatedly stated that many secondary students have little identification with the science that is taught at school. Studies point out students‟ lack of interest, scarce previous knowledge to understand science content, and poor learning outcomes. This state of affairs is more evident in schools with students with a weak socio-economic background, who are at a disadvantage in terms of the cultural capital that school legitimates In this paper we intend to shed light on this issue from four theoretical perspectives: the theoretical framework of "public understanding of science‟; views from the sociology of education ("labelling theory‟ and "self-fulfilling prophecy‟); the so-called "cultural perspectives‟ in didactics of science (i.e. science education as a discipline); and fourthly, a perspective founded on the philosophy of science: teachers‟ images of science from a model-based view.